Managing State Debt and Ensuring Solvency : The Indian Experience - Rangarajan, C.; Prasad, Abha (World Bank, Washington, DC, 2012)
The paper presents the policymakers perspective on the reforms undertaken to manage states debt and ensure solvency. While the sustained high growth rates of the Indian economy played a part in alleviating the interest burden on debt and ensuring that the debt does not grow in an explosive trajectory, major reforms were implemented to reverse the fiscal decline, develop fiscal responsibility rules to ensure sustained adjustment, and move toward a market-based financing of state deficits. The serious efforts at fiscal consolidation and institutional reforms have enabled states to set on the path toward fiscal correction. Nonetheless, weak global growth prospects and the risk of a further rise in global commodity and fuel prices could generate the dilemma of needing to compress expenditures for ensuring fiscal sustainability while simultaneously needing counter-cyclical spending to boost growth, and challenge the fiscal adjustment process.